Asymmetries in import-retail cost pass-through: Analysis of the seafood value chain in Germany. Issue 1 (2nd January 2017) - Ankamah-Yeboah, Isaac; Bronnmann, Julia
ABSTRACT: This study examines the degree of price transmission in the German Alaska pollock, cod and salmon value chains. Moreover, in addition to aggregated market prices used in most studies, access to prices by retailer type allows investigation of different adjustment patterns by value chain. Using monthly average prices, the Johansen and consistent threshold cointegration models are estimated. The results indicate the presence of price transmission relationship and equilibrium adjustment asymmetries, such that agents only react to shocks when the deviation from equilibrium is above or below a certain nonzero threshold value. In most cases, retail outlets exercise market leadership in the Alaska pollock and cod chains while some bidirectional adjustments are observed in the salmon value chains. Overall, import prices adjust to deviations above the threshold value following a shock to the retail prices for Alaska pollock and cod. For salmon, deviations above the threshold value are generally not transmitted.